Combining Sensor and Protective Functionalities in Ferromagnetic Nanocomposite Thin Films for Applications in Harsh Environments1 . Issue 5 (1st February 2016) - Seemann, Klaus; Leiste, Harald; Stüber, Michael; Krüger, Kathrin; Brunken, Hayo; Ludwig, Alfred; Thede, Claas; Quandt, Eckhard
Abstract : The present paper discusses the development of Fe48 Co52 /TiN, Fe32 Co44 Hf12 N12 /TiN, Fe–Co/Al–N multilayer, and Fe2 B single layer films produced by magnetron sputtering processes. These films combine appropriate magnetic and wear resistant multifunctional properties for the employment as sensor components for monitoring the actual state of stress and/or temperature of cutting tools used in the metal processing industry. At this point, the ferromagnetic layers enable the sensor function, whereas the TiN or Al–N layers support mechanical features. Being exposed to stress and/or temperature, the change of polarization or permeability can be utilized as a response for reading‐out the sensor component. Abstract : The paper introduces the development of Fe48 Co52 /TiN, Fe32 Co44 Hf12 N12 /TiN, Fe–Co/Al–N multilayer, and Fe2 B single layer films as sensor components for monitoring, e.g., the actual state of stress and/or temperature of cutting tools which are used in metal processing. The films are produced by magnetron sputtering processes. They ought to combine appropriate magnetic property changes and wear resistance.